EFFECTIVE USE OF INFORMATION TECHNOLOGY IN TEACHING CHILDREN (Euro-Asia Conferences, 2021)
No part of our lives today can be imagined without informationtechnology. Therefore, the effective upbringing of future generations onthe basis of modern technologies has become a modern requirement.